A longitudinal mixed-methods examination of emotional intelligence, mindfulness, and burnout among Chinese educators - Han, Xiao; Jiao, Mingmu; Perey, Gemma M. (Frontiers in Psychology, 2025)
IntroductionThis longitudinal mixed-methods study explored the interplay between emotional intelligence (EI), mindfulness practices, and burnout among secondary school educators in mainland China. The aim was to understand changes in these variables over time and the impact of mindfulness.MethodsThe study tracked EI Wong and Law Emotional Intelligence Scale (WLEIS) and burnout Maslach Burnout Inventory - Educators Survey (MBI-ES) quantitatively over 12 months in a sample of 216 educators (189 completed all phases). Qualitative data were gathered through semi-structured interviews with 35 participants to explore lived experiences.ResultsQuantitative findings revealed a significant reduction in emotional exhaustion and depersonalization, while EI facets remained stable. Average daily mindfulness-practice duration was inversely correlated with emotional exhaustion (r = −0.28, p = 0.003). Qualitative analysis highlighted themes including the multifaceted burden of burnout, the perceived role of EI, mindfulness as a coping tool, personal coping mechanisms, high self-awareness alongside challenges in emotional regulation, and the impact of systemic stressors. Practical constraints reportedly limited sustained mindfulness engagement.DiscussionThe findings contribute to understanding the complex interactions between EI, mindfulness, and burnout in educators. This study offers insights into potential strategies for fostering teacher resilience and well-being within educational settings, emphasizing the benefits of mindfulness for emotional exhaustion while acknowledging limitations.